Seed Priming: an Efficient Farmers’ Technology to Improve Seedling Vigour, Seedling Establishment and Crop Productivity - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2011)
Poor seedling emergence and seedling vigour affect crop productivity in farmers’ field. This urgez the necessity of simple, feasible and viable technology to improve seedling vigour and seedling establishment of crops under all environmental conditions. Rapid and uniform field emergence are two essential prerequisites to increase yield and quality in crops. Uniformity and increased seedling emergence of direct-seeded crops have major impact on final yield and quality (Gupta et al., 2008). Seed priming is a pre-sowing seed treatment that involves the controlled hydration of seeds, sufficient to allow pre-germinative metabolic events to take place, but radical emergence does not occur (Heydecker, 1937, Bradford, 1986). Priming allows the metabolic processes necessary for germination without protrusion of radicle. Priming is an enhancement method that accelerates germination and emergence (Khan, 1992; Taylor, 1998). Increased germination rate and uniformity have been attained due to metabolic repair during imbibitions.